Tatalaksana Anestesi pada Mandibulektomi Rekonstruksi pada Adenokarsinoma Mandibula - ari wahyuni; Brandon Caesario (Medula, 2021)
Metastatic carcinoma on mandibula is a very rare lesion, contributing to <1% of all oral malignancies. Usually metastatis originate from breast, lungs, prostate, followed by kidney, thyroid, liver, etc. Carcinoma type lesion is more common than sarcomas. Mandibular metastation from thyroid tumors were very rare, and follicular type was the most common. In maxillofacial surgeries, airway management is very important considering difficult airway is commonly present. Either caused by altered surrounding tissues, organ immobilities, or organ enlargements. A 58-year old woman, weighing 45 kgs, and 159 cm in height was admitted to Dr. dr. H. Abdoel Moeloek Hospital of Lampung Province with a lump on right jaw from 1 year ago. On physical examination, the tumor was 7x5 cm in size, immobile, with firm consistency. Histopathology examination reveal an adenocarcinoma. Patient was diagnosed with mandibular adenocarcinoma and reconstructive mandibulectomy was performed.